2020
DOI: 10.1109/access.2020.3011989
|View full text |Cite
|
Sign up to set email alerts
|

Point Cloud Reduction and Denoising Based on Optimized Downsampling and Bilateral Filtering

Abstract: The project was funded by jinan science and technology bureau and undertaken by qilu university of technology, Machine vision-based online intelligent detection of foreign objects in liquids is implemented.2019GXRC067.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In our method, first, in order to solve the damage of the point cloud surface structure caused by downsampling, the FWD method is adopted.The spatial structure of the point cloud is preserved by this method [6],the effect is better than existing methods.Secondly, in order to further improve the accuracy of the search method, a new search method KK octant search is proposed.On the basis of octant search, the threshold is set to further filter, so that the obtained points are more suitable for the same characteristics.The most important point is the problem of the correlation between adjacent coordinates and the input, and the problem of difficult segmentation of multiple connected regions.A combination of multiple features is proposed to fully extract spatial and geometric information,compared with the latest method SAN, better performance is achieved.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our method, first, in order to solve the damage of the point cloud surface structure caused by downsampling, the FWD method is adopted.The spatial structure of the point cloud is preserved by this method [6],the effect is better than existing methods.Secondly, in order to further improve the accuracy of the search method, a new search method KK octant search is proposed.On the basis of octant search, the threshold is set to further filter, so that the obtained points are more suitable for the same characteristics.The most important point is the problem of the correlation between adjacent coordinates and the input, and the problem of difficult segmentation of multiple connected regions.A combination of multiple features is proposed to fully extract spatial and geometric information,compared with the latest method SAN, better performance is achieved.…”
Section: Introductionmentioning
confidence: 93%
“…FWD uses a combination of farthest-point sampling and down-sampling. Compared with only farthest-point sampling, more suitable samples can be taken; the effect of FWD has been proved by [6]. In Fig.…”
Section: A Multi-scale Feature Framework(mff)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the above article [1], when we edited the affiliations of authors, their old names were provided and the new names were not added. As a result, when other researchers queried the authors of [1], the affiliations of authors were not found due to the incorrect affiliations in the article [1]. These affiliations caused incomplete information.…”
mentioning
confidence: 99%
“…In this article, the affiliations of authors are corrected by us. After affiliations are revised, the affiliations do not affect the results and analysis of the article [1].…”
mentioning
confidence: 99%